Differential severity of LPS-induced lung injury in CD26/DPP4 positive and deficient F344 rats - Zientara, Alicja; Stephan, Michael; von Hörsten, Stephan; Schmiedl, Andreas (Histology and Histopathology, 2019)
BACKGROUND: Lipopolysaccharide (LPS) induced inflammation often leads to lung injury, in which pulmonary recruitment of neutrophils plays a pivotal role. Inflammatory processes are influenced by CD26/DPP4, highly expressed in lungs. Asthma induced CD26/DPP4 deficient (CD26/DPP4⁻) Fischer (F) 344 rats suffering from a transport block in the rER caused by a point mutation showed reduced pulmonary inflammation and reduced expression of immunomodulating surfactant proteins (SP). The degree of LPS induced lung injury in CD26/DPP4 deficient rats has not been investigated so far. OBJECTIVE: We hypothesize that LPS induced lung injury leads not only to an attenuated inflammation but also to a reduced SP expression and decreased structural damage in CD26/DPP4⁻ rats. METHODS: Both genotypes were intratracheally instilled with 250 µl LPS or with 250 µl 0.9% NaCl. Nine hours later animals were killed and either bronchoalveolar lavage was carried out to determine inflammatory cells and surface tension or lung blocks were removed and processed for histology, immunohistochemistry, electron microscopy or qRt-PCR analyses and Western Blot analyses. RESULTS: Signs of acute lung injury, such as structural damage of the blood gas barrier occurred only sporadically in both genotypes. LPS-induced CD26/DPP4⁻ rats showed decreased gene expression of SP-A and SP-D and reduced signs of lung inflammation associated with a reduced alveolar influx of macrophages and neutrophils. CONCLUSIONS: Less pulmonary inflammation combined with less structural alterations and minor expression of immunomodulating SP may be an indication of the critical role of CD26/DPP4 in regulating lung inflammation.
CRIS-Team Scopus Importer:2019-10-15